DEVELOPMENT AND VALIDATION OF VOCATIONAL LITERACY-BASED LEARNING MODELS - Arthur, Riyan; Sunita, Sunita; Maulana, Arris; Murtinughara, Eka (Universitas Labuhanbatu, 2025)
Purpose – The development of technology presents new challenges, along with the weakening of literacy culture. In the learning process at SMK, project-based learning still uses conventional models, and students still do not understand them. The drawback is in the syntax used; a leap in stages should allow students to explore the product first. On the other hand, literacy has a strategic role in developing the competencies of Vocational High School students. This study aims to develop a vocational literacy-based learning model in vocational schools.Methodology—The research method used is the Traditional mix method, which is limited to the stage of development (development) and expert validation by involving experts in the fields of learning design and language. The result of this study is the syntax of a vocational literacy-based learning model.Findings—The final validation analysis by experts yielded validity values of 0.80 (learning design) and 0.79 (language).Significance—This means that this vocational literacy-based learning model is feasible for use in teaching and learning activities at the vocational level. Keywords : Vocational Literacy, Vocational High School, Learning Model